Constitutional procedural activism (Revista do Tribunal Regional Federal da 3ª Região, 2015)
The position of the Federal Supreme Court (STF) in Brazil's political structure makes it the supreme interpreter of the Constitution. It interprets with supremacy not only material constitutional law, but also procedural constitutional law. If the STF's ability to create substantive constitutional law is undeniable, in a context of timid constitutional procedural legislation such as Brazil's, it is even more so because it provides an even wider field for constitutional procedural activism. Despite its importance, this topic is still surprising due to its lack of research in Brazilian doctrine, compared to the interest it has long aroused in other countries. The idea of constitutional procedural activism is used here in the sense of the STF's active role in the production of constitutional procedural norms. Peter Häberle detects this movement in the German Federal Constitutional Court when he says that it is possible to rework German constitutional procedural law based on case law. These considerations show that constitutional jurisprudence is a special form of judicial production of constitutional procedural statutes, the understanding of which requires appropriate interpretative approaches that differ from those traditionally practiced in civil law legal systems. Special attention should be paid to these inferences in Brazil, due to the legislative profile favoring the STF's power to shape the law.Translated with DeepL.com (free version)
Keywords: procedural activism; STF; parameters of positive action; conformation of the constitutional process; constitucional procedural autonomy; legitimacy; motivation